2008
DOI: 10.1021/jm801157z
|View full text |Cite
|
Sign up to set email alerts
|

Berberine Analogues as a Novel Class of the Low-Density-Lipoprotein Receptor Up-Regulators: Synthesis, Structure−Activity Relationships, and Cholesterol-Lowering Efficacy

Abstract: Twenty-nine derivatives of berberine (1) or pseudoberberine (2) were designed, semisynthesized, and evaluated for their up-regulatory activity on the low-density-lipoprotein receptor (LDLR) expression. SAR analysis revealed that (i) the methylenedioxy group at the 2- and 3-position is an essential element to keep the activity, (ii) the 7-position quaternary ammonium and planar structure of the compound are activity-required, and (iii) addition of electron-donating groups at the 7- or 13-position reduced the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(38 citation statements)
references
References 18 publications
2
35
0
Order By: Relevance
“…2,3) Many studies have shown that BBR exhibits multiple pharmacological activities including antioxidant, anti-microbial, anti-tumor, and cholesterol-lowering effects. [4][5][6][7] Our previous studies found that BBR could reinforce the intestinal epithelial tight junction and reduce epithelial intestinal permeability in vitro and in vivo, which is important to maintain the intestinal mucosal barrier function. [8][9][10] Therefore, in order to further explore the protective effect of BBR on the intestinal mucosal barrier damage induced by peritoneal air exposure, it is important to determinate the changes in the intestinal mucosa barrier function during peritoneal air exposure under experimental conditions mimicking clinical operation room atmosphere.…”
Section: Discussionmentioning
confidence: 99%
“…2,3) Many studies have shown that BBR exhibits multiple pharmacological activities including antioxidant, anti-microbial, anti-tumor, and cholesterol-lowering effects. [4][5][6][7] Our previous studies found that BBR could reinforce the intestinal epithelial tight junction and reduce epithelial intestinal permeability in vitro and in vivo, which is important to maintain the intestinal mucosal barrier function. [8][9][10] Therefore, in order to further explore the protective effect of BBR on the intestinal mucosal barrier damage induced by peritoneal air exposure, it is important to determinate the changes in the intestinal mucosa barrier function during peritoneal air exposure under experimental conditions mimicking clinical operation room atmosphere.…”
Section: Discussionmentioning
confidence: 99%
“…Second, BBR can bind to nucleic acids, such as dsRNA. As miRNA molecules play a key role in controlling the expression of different genes, BBR in its planar form [57] might bind to grooves on the 3D structure of RNA [55,56].…”
Section: Perspectivesmentioning
confidence: 99%
“…Vanillin rich fraction (VRF) extracted from vanilla pods increased Ldlr mRNA in a dosedependent manner in HepG2 cells (Al-Naqeb et al, 2010). Berberine (BBR), a compound isolated from a Chinese herb, was observed to increase Ldlr expression and reduce serum cholesterol and LDL-C in hyperlipidemic hamsters (Kong et al, 2004), with similar effects observed in HepG2 cells (Abidi et al, 2006;Li et al, 2009). …”
Section: Ldlrmentioning
confidence: 84%